ANALISIS REGRESI PANEL TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI KALIMANTAN SELATAN TAHUN 2018-2022 - Ade Irawan; Herlina Wati; Nur Salam; Al Hujjah Asianingrum (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the effects of population growth rate, Human Development Index (HDI), and per capita expenditure on poverty levels in 13 regencies/cities of South Kalimantan Province during the period 2018–2022. The study uses secondary data obtained from the Central Bureau of Statistics and applies panel data regression using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Model selection was conducted using the Chow test, Breusch–Pagan Lagrange Multiplier test, and Hausman test, as well as considering variable significance and model explanatory power. The results indicate that the Fixed Effect Model with time effects (FEM-time) is the most appropriate model. Initial estimation results show that population growth rate and per capita expenditure have significant negative effects on poverty, while HDI has a significant positive effect. However, after applying robust standard errors to address autocorrelation and heteroskedasticity, only per capita expenditure remains statistically significant. These findings suggest that improvements in household purchasing power play a central role in reducing poverty in South Kalimantan, while the impacts of demographic and human development factors tend to vary over time. This study is expected to provide empirical evidence to support more adaptive and region-specific poverty alleviation policies.